Data Needs for Emerging Research Issues in Bully and Violence Prevention - Dorothy Espelage (SAGE Publishing, 2015)
School violence and bullying are two public health concerns with consequences for youth in and out of school, for families, students, and community members. In this article, a social-ecological framework is briefly described as a way to understand bullying and school violence; then the National Center for Educational Statistics (NCES) longitudinal and cross-sectional data sets are described in detail. Data that assess bullying and/or school violence are described, and recommendations for additional items are proposed. In general, a longitudinal, multisite, multi-informant study is needed to address definitional and etiological issues related to school violence and bullying so that prevention efforts can be developed, implemented, and evaluated that incorporate multiple levels of the ecology, including peers, schools, communities, and neighborhoods.